If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -1b = 2(x + -4) Reorder the terms: Y + -1b = 2(-4 + x) Y + -1b = (-4 * 2 + x * 2) Y + -1b = (-8 + 2x) Solving Y + -1b = -8 + 2x Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add 'b' to each side of the equation. Y + -1b + b = -8 + b + 2x Combine like terms: -1b + b = 0 Y + 0 = -8 + b + 2x Y = -8 + b + 2x Simplifying Y = -8 + b + 2x
| 7+2=7x-3 | | 4+78=39x+40 | | 6=6x-5x | | 2x-24=-3x | | 6x-24=x | | 4x-7=8x+4 | | 4t-8t=-5 | | 4t-8whent=-5 | | 31-6x=13-9x | | 120+6x=6x | | T(n)=30-5n | | 6t+13=2t+17 | | 4/7=9/a-7 | | 12=-16x | | 31=13-3x | | log(x^2-15x)=3 | | 5p^1=81 | | W+5=w+2 | | 6t-5=3t+10 | | 5a+6=2a+24 | | 3(k+6)=30 | | 10x=3x+3 | | (2x-3)2-(11-x)2+(7-4x)(7+4x)= | | 5-5X=23-2X | | 30-4(3x+2)=9 | | 72=2(w-6)+2w | | 5(2x+5)=31(7+2x) | | 5i-6=14 | | 180y-360-3y^2+6y=120y | | 8+2x=x | | 33-3x=13-8x | | 4s+8=6(s+1) |